Dimensional and Surface Texture Characterization in Fused Deposition Modelling (FDM) with ABS plus. (2015) - Nuñez, P.J.; Rivas, A.; García-Plaza, E.; Beamud, E.; Sanz-Lobera, A.
Abstract: Fused Deposition Modelling (FDM) has become extensively used for low-cost printers. Normally, commercial manufacturers of printers only provide information on layer thickness, but no information is given as to dimensional accuracy, and the surface characteristics obtained in manufactured components. The aim of this study was to determine the dimensional accuracy, flatness, and surface texture obtained in FDM rapid prototype with ABS-plus as the model material. In the experimental test, two densities (low, solid) and two layer thicknesses (0.178 mm, 0.254 mm) were used. The best dimensional behaviour was obtained with the configuration of maximum layer thickness (0.254 mm) and solid density (100%) with a maximum deviation length of 〛 36 μm. The best finish surface and minimum flatness error were obtained with less layer thickness (0.178 mm) and solid density (100%). This study has established the optimum configurations for the manufacture of components with FDM 3D printing and ABS-plus.